Nilai Tambah Produk Olahan Ikan Salmon di PT Prasetya Agung Cahaya Utama, Kecamatan Kediri, Kabupaten Tabanan - PRAMANA, I PUTU RIDIA; SUDARMA, I MADE; ARTINI, NI WAYAN PUTU (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.4, No.1, Januari 2015, 2016)
Abstract The Added Value on the Product of Processed Salmon Fish at PT Prasetya Agung Cahaya Utama, Sub-district of Kediri, Regency of Tabanan. PT Prasetya Agung Cahaya Utama is a company which running the business of processing salmon fish into smoked salmon so that providing added value of the product. The aim of this research is to find out the added value of salmon fish as a raw material for smoked salmon and to find out the BEP value in the one year production. The result of research shows that the processing of smoked salmon in the export market providing more added value that is at Rp 82,930.12/kg of frozen salmon compares to the added value of smoked salmon in domestic market at the price of R p 57,930.12/kg of frozen salmon. The result of BEP analysis shows that the break event point of smoked salmon quantity at the domestic market in the year of 2013 at 263.26 kg with the break event of selling price at Rp. 192,496.52/kg of smoked salmon. Further the break event quantity of smoked salmon for export market at 179.76 kg and the break event of selling price at Rp. 197,087.01/kg of smoked salmon. Financially the processing of salmon fish into smoked salmon has provided the profit for the company, but on the other hand the company has a constraint for the import value which depends on the exchange rate of Rupiah to the US Dollar. Key words: Added value, BEP, Salmon